Digital opportunities for change [WOUGNET] - Achora, Janet C.; Ngolobe, Berna (Technical Centre for Agricultural and Rural Cooperation, 2009)
Since 2000, the Women of Uganda Network has been developed a wide range of initiatives to improve access to ICTs for women farmers and entrepreneurs.